Science 1998
DOI: 10.1126/science.282.5395.1858
|View full text |Cite
|
Sign up to set email alerts
|

A 25,000-Year Tropical Climate History from Bolivian Ice Cores

Abstract: Ice cores that were recovered from the summit of Sajama mountain in Bolivia provide carbon-14-dated tropical records and extend to the Late Glacial Stage (LGS). Oxygen isotopic ratios of the ice decreased 5.4 per mil between the early Holocene and the Last Glacial Maximum, which is consistent with values from other ice cores. The abrupt onset and termination of a Younger Dryas-type event suggest atmospheric processes as the probable drivers. Regional accumulation increased during the LGS, during deglaciation, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

23
457
2
14

Year Published

1999
1999
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 731 publications
(506 citation statements)
references
References 37 publications
23
457
2
14
Order By: Relevance
“…[40] These results presented here have a bearing on the interpretation of the stable isotope ratios in tropical ice cores [e.g., Thompson et al, 1995Thompson et al, , 1998]. Interpretations of changes in stable isotope ratios of ice cores have assumed that the oceanic source vapors were in near isotopic equilibrium with the sea surface .…”
Section: Discussionmentioning
confidence: 99%
“…[40] These results presented here have a bearing on the interpretation of the stable isotope ratios in tropical ice cores [e.g., Thompson et al, 1995Thompson et al, , 1998]. Interpretations of changes in stable isotope ratios of ice cores have assumed that the oceanic source vapors were in near isotopic equilibrium with the sea surface .…”
Section: Discussionmentioning
confidence: 99%
“…However, as the ice records (e.g. Dansgaard et al, 1993;Thompson et al, 1998) and ocean records (e.g. Bond et al, 1993;Friedrich et al, 2001) have demonstrated, Pleistocene temperatures were far from constant.…”
Section: Discussionmentioning
confidence: 99%
“…For several regions of the globe, including the tropics, it is now clear that the transition to modern climate following the last glacial maximum was punctuated by a number of rapid and substantial climatic oscillations (Alley et al, 1993;Gasse and Vancampo, 1994;Thompson et al, 1998). In contrast, relatively little is known about how the tropical ocean responded to the deglaciation because few high resolution records are available from these regions (Hughen et al, 1996).…”
Section: Post-glacial Tropical Sstsmentioning
confidence: 99%